No Association of Polymorphisms in the Dopamine Receptor D2 (DRD2) Gene with Cold Pressor Pain Sensitivity among Healthy Malay Males - Nasir, Mohamad; Zalina, Zahari; Chee Siong, Lee (2015)
Objective: To examine the effects of variations of loci in the dopamine receptor D2 (DRD2) gene on cold pressor pain responses among healthy Malay males.